Economic forecasts and sovereign yields - Afonso, António (2015)
We assess whether the correctionsmade to the EC macro and fiscal forecasts (GDP growth rate, inflation, budget balance, debt ratio, current account) have an impact in sovereign yields. We perform a panel analysis of 15 EU countries (Austria, Belgium, Germany, Denmark, Spain, Finland, France, United Kingdom, Greece, Ireland, Italy, Luxembourg, Netherlands, Portugal and Sweden), for the period from 1999:1 until 2012:1, and we also analyse each country individually, on the basis of a SUR estimation.We find that corrections in the EC's forecasts impinge on 10-year sovereign bond yields, particularly corrections in fiscal variables, beingmore pronounced in countries with less favourable economic conditions. The penalization for the yields is higher in corrections for the current and next years than for previous years.